Dividend policy of public companies in Bosnia and Herzegovina - Ante Dzidic (UTMS Journal of Economics, 2014)
This paper provides insight in dividend policy of publicly listed companies in Bosnia and Herzegovina and investigates appearance of dividend smoothing behavior. The results show increase in portion of dividend paying companies over time while dividend smoothing phenomenon is virtually non-existent. On the other hand, when companies decide to pay dividends they, on average, distribute high portion of profit to shareholders. The paper also provides discussion about capital market development, investor protection and ownership concentration as potential factors affecting importance of dividend payouts. Research results indicate that insufficiently developed capital market characterized with low investor protection and concentrated ownership structure undermine the importance of dividend smoothing practices.
Keywords: G35; 330; dividends; dividend policy; dividend stability; dividend smoothing behavior; capital market development